Máscara da desigualdade social: o Banco Mundial e a Política de Assistência Social - Vidal, Karina Caputti (2021)
This research seeks to apprehend how social protection manifests itself in the Brazilian socio-historical context, discussing the inclusion of the Social Assistance Policy in the process of reproduction of the workforce. The objective of this study is to investigate the determinations imposed by capitalist rationality in the peripheral and dependent reality, in which social policies (with emphasis on Social Assistance) do not alter the process of capital accumulation and appreciation and, on the contrary, are used as a “Lever” for the capitalist order. In this sense, the research presents the determinations mobilized by capitalist procedurality and considers the World Bank as an element of mediation for analysis, since such a multilateral agency presents itself as a political and ideological actor in the formulation, determination and institutionalization of social policies for the periphery capitalist. In this way, we started from the economic and political apprehension to demystify the mechanisms of big capital that mask the expressions of the “social issue” in a fragmented, simplistic and obscurantist way in the organization of capitalist sociability. The theoretical and methodological assumptions of the research are based on the theoretical, documentary and data analysis of social policies and the manifestations of the “social issue”, including poverty, social inequality and structural unemployment. The present study identifies social policies as an expression of social reproduction legitimized by the bourgeois state and observes that only in appearance are they driven by the separation between the economic and the political through automated processes, since the theoretical trajectory of this research indicates that these dimensions are not only they are related, as they are fundamental in the way that capitalism presents itself in all manifestations of life. The social role played by social policies (and particularly Social Assistance) in the current development of capitalism is a guarantee for the very dynamics of capital accumulation. In addition, the research identifies the intrinsic relationship between the Social Assistance Policy and the World Bank (in its process of implantation, implementation, expansion, institutionalization and theoretical content) and analyzes how it is used in the process of reproducing the workforce. The growing social deprotection characteristic of the requirements of the financialized capital phase demonstrates that “democratizing” social policies are incompatible with the current needs of capitalism, causing a process of emptying, destruction and weakening of social guarantees in which capitalism intensifies social expropriation and keeps the reproduction of the workforce at the limit of survival